Cross-border acquisition of the ownership of agricultural lands and some topical issues of the Hungarian law - Szilágyi, János Ede (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Abstract: While Serbia is working on a new EU-conform land law, the EU law concerning the cross-border acquisition of agricultural lands cannot be considered as a static phenomenon. Namely, the issue is quite controversial among the EU’s institutions and Member States. Evidence of this is the high number of infringement procedures launched by the EU Commission against the Member States joined the EU in 2004 or afterwards (hereinafter referred to as New Member States). However, it is worth stressing that the debate is not merely a New-Member-State-issue but a general one, and there are numerous uncertainties which may affect even the old Member States’ land law regimes. That is the reason (or one of the most important reasons) why the European Parliament adopted a report on the state of play of farmland concentration in the EU in 2017. It seems that nowadays land issues have also become one of the topical questions of the EU, which questions could be raised because the EU is in a kind of the crisis. The EU should redefine itself and its goals, furthermore, it also should determine a new structure in numerous parts of life. The European Council for Rural Law (more usually known as the CEDR from its French name „Comité Européen de Droit Rural”), a think-tank which regularly provides assistance and advice to the institutions of the European Union, also dealt with the cross-border land law issues of the EU; namely, in a commission (COM II) concerning rural areas of the CEDR Congress (Potsdam, 2015) and at the conference on the 60th anniversary of the CEDR (Brussels, 2017). In a Hungarian conference (Budapest, 2017), the legal experts were gathered by the Hungarian Association for Agricultural Law and the Public Law Sub-Commission of the Hungarian Academy of Sciences in order that they could present the possible ways of the improvement for the EU and its Member States. With regard to this development, the present article focuses on the EU’s main rules concerning the acquisition of agricultural lands, the infringement procedures against Hungary (hereinafter referred to as Hungarian cases), the report of the European Parliament and the general conclusions of the Budapest conference. The Hungarian cases are relevant not merely for Hungary as the European Commission has expressed its concerns about the most of regulations of the Hungarian land law in comparison with other concerned New Member States. Taking the low numbers of the CJEU cases (concerning land law) into consideration, the Hungarian cases might be significant for the whole of the EU and its future.